PENATAAN KAMPUNG WISATA TEMATIK PULO GEULIS, KELURAHAN BABAKAN PASAR, KECAMATAN BOGOR TENGAH, KOTA BOGOR - Adiba Handari; Priyendiswara Agustina Bella (Jurusan Arsitektur dan Perencanaan, 2022)
Bogor City is one of the cities in West Java Province. This city has the potential as a tourist city, with a wide selection of types of tourism in the city of Bogor, besides its location is also not far from the capital city of Indonesia. The city of Bogor has a characteristic that it is one of the most popular cities because it is famous for its natural attractions. In addition, the city of Bogor also saves a lot of history and other uniqueness. But day by day, the high demand for housing is increasing, so that more and more slums appear in the city of Bogor. Seeing this phenomenon, the Bogor City Government has a plan to develop Thematic Tourism Areas that are in accordance with the conditions of each region. This effort is made to improve the quality of life, welfare, and to support the economy of the city of Bogor. One of them is Kampung Pulo Geulis, this village has a high historical value. So that the Bogor City Government has designated it as one of the Thematic Tourism Villages, whose direction is to introduce history and also a form of real tolerance for the people in Pulo Geulis Village. However, a good Thematic Tourism Village has not yet been realized due to a lack of coordination, communication, and appropriate proposals between residents, the Government, and the Private Party. In addition, the lack of facilities and infrastructure that can support the formation of the Tourism Village in Pulo Geulis, the absence of shared open spaces makes tourism activities in Pulo Geulis not optimal. This research is a descriptive study using a qualitative approach. The data were obtained from the results of interviews, surveys of the object of study, and observing the existing data. Interviews were conducted with the Secretary of the Babakan Pasar Village, the Head of RW 04, the Head of Pokdarwis, the Head of the RT, and also the residents of Kampung Pulo Geulis. Based on the results of the analysis, the Kampung Pulo Geulis area already has potential that can be developed to become a Tourism Village. The author conducted several analyzes including location and site analysis, where the analysis aims to determine environmental conditions, land use plans, and appropriate structuring plans for Kampung Pulo Geulis. Keywords: Arrangement; Tourism Village; Thematic Village; Facilities and infrastructure Abstrak Kota Bogor adalah salah satu Kota yang terdapat di Provinsi Jawa Barat. Kota ini memiliki potensi sebagai Kota wisata, dengan beragam pilihan jenis wisata yang terdapat di Kota Bogor, selain itu lokasinya juga tidak jauh dari Ibu Kota. Kota Bogor memiliki ciri khas yaitu merupakan salah satu Kota yang di gemari karena terkenal dengan wisata alamnya. Selain itu, Kota Bogor juga menyimpan banyak sejarah dan keunikan lainnya. Namun semakin hari, tingginya kebutuhan akan hunian semakin meningkat, sehingga semakin banyak permukiman kumuh di Kota Bogor. Melihat fenomena ini, Pemerintah Kota Bogor memiliki rencana untuk mengembangkan Kawasan Wisata Tematik yang sesuai dengan kondisi masing-masing wilayahnya. Upaya ini dilakukan guna meningkatkan kualitas hidup, kesejahteraan, serta untuk menunjang perekonomian Kota Bogor. Salah satunya adalah Kampung Pulo Geulis, kampung ini memiliki nilai sejarah yang tinggi. Sehingga Pemerintah Kota Bogor menetapkannya sebagai salah satu Kampung Wisata Tematik, yang dimana arahnya adalah untuk memperkenalkan sejarah dan juga wujud toleransi nyata masyarakat yang terdapat di Kampung Pulo Geulis. Namun belum terwujudnya Kampung Wisata Tematik yang baik dikarenakan kurangnya koordinasi, komunikasi, serta usulan yang tepat antara warga, Pemerintah, dan Pihak Swasta. Selain itu, minimnya sarana dan prasarana yang mampu menunjang terbentuknya Kampung Wisata di Pulo Geulis, tidak adanya ruang terbuka bersama membuat kegiatan wisata di Pulo Geulis menjadi tidak maksimal. Penelitian ini merupakan penelitian deskriptif dengan menggunakan pendekatan kualitatif. Data-data diperoleh dari hasil wawancara, survei terhadap objek studi, dan melakukan observasi terhadap data-data yang ada. Berdasarkan hasil analisis, kawasan Kampung Pulo Geulis sudah memiliki potensi yang dapat dikembangkan untuk menjadi Kampung Wisata.